Penentuan Calon Penerima Program Keluarga Harapan (PKH) Dengan Metode Analytical Hierarchy Process (AHP) - Agi Kakana Bangun; Yani Maulita; Suci Ramadani (Bulletin of Multi-Disciplinary Science and Applied Technology, 2023)
Poverty is a situation where there is a lack of ordinary things to have such as food, clothing, shelter and drinking water. Poverty sometimes also means a lack of access to education and employment that can overcome the problem of poverty and gain the respect one deserves as a citizen. Poverty itself in developing countries is quite a complicated problem even though several developing countries have succeeded in implementing development in terms of production and national income. One of the government's social assistance-based programs is the Family Hope Program (PKH). To overcome the above problems, it is necessary to build a system that can make it easier for Kuala District, Langkat Regency to make decisions about recipients of PKH assistance. To support accuracy in building a decision-making system, a method is needed that is capable of making the right decisions based on predetermined criteria. In this research, the method used is AHP. Analytic Hierarchy Process (AHP) is a structured method for managing and analyzing complex decisions using mathematical and psychological concepts. The AHP method helps in determining the priority weight of each parameter that is taken into consideration in making decisions. Based on the value of importance of criteria and sub-criteria from 10 alternative data, the highest value was obtained, namely alternative recipient 8 with a system analysis value of 0.2105 with the income criterion of the head of the family being IDR. 2,657,000, Head of family's education is high school, well water source, home toilet, boarded house building, parent's house ownership status, number of dependents 3 people, number of dependents Education of children 3 people, owns a motorbike